La production culturelle pour la jeunesse au prisme du dépôt légal - Alice Laforêt (Strenae)
Every year, the Bibliothèque nationale de France publishes its Observatoire du dépôt légal, a publication that sheds light on the publishing world and its trends in terms of the documents and resources received under legal deposit. The 2018 edition focused on cultural production for children. The purpose of this article is to revisit the topic of youth in the bibliographic data of the BnF and to propose avenues and methodologies for exploiting this data.